C29 SEEING BEYOND APPEARANCES: INTRACORONARY IMAGING TECHNIQUES IN SPONTANEOUS CORONARY ARTERY DISSECTION (SCAD). (18th May 2022) - Desario, P; Rutigliano, D; Basso, P; Palumbo, V; Ricci, G; Sublimi Saponetti, L; Locuratolo, N; Caldarola, P
Abstract: Over recent years, mainly due to a broad use of coronary angiography and intracoronary imaging techniques (IIT), SCAD has emerged as a no longer rare cause of acute coronary syndrome (ACS). Early diagnosis is extremely important to avoid potentially lethal complications; nevertheless, considerable uncertainty remains about optimal acute and post–discharge management. Current endorsed therapeutic strategy lean towards an initial conservative approach, relegating percutaneous or surgical coronary intervention to high–risk coronary anatomy or in case of hemodynamic instability. We report our experience in the field by presenting a clinical case of a 36–year–old woman admitted to emergency department with acute, anginal pain started 24 hours earlier, referring no medical history, except for a syncopal episode occurred four days earlier, in correspondence of a mournful event. She was hemodynamically stable, with work–up significant only for elevated troponin level of 3649.5 ng/ml (n.v. <11). Coronary angiogram showed atherosclerotic–like changes limited to right coronary artery (RCA), with focal subcritical stenosis at its proximal segment (Fig 1 ). In the absence of major precipitating factors for atherosclerotic coronary disease, SCAD was suspected. IVUS and OCT were performed, with evidence of dissection and intra–mural haematoma (Fig. 2), extending from proximal RCA to posterior descending branch take–off, compressing the true lumen. Considering both anatomical (coronary ostium not involved) and clinical (patient asymptomatic and hemodynamically stable) factors, conservative treatment with low dose aspirin and beta blocker was prescribed. After three days of hospitalization occurred a single episode, lasted 5 minutes, of anginal pain associated with ST elevation in inferior leads, managed with nitrates administration; subsequent cardiac computed tomography angiography excluded disease progression (Fig.2 ). On the 23rd day, due to angiographic evidence of SCAD partial healing (Fig.3 ), the patient was discharged. This case highlights the importance of keeping in mind the possibility of SCAD, especially when healthy young women with prior emotional stress present with ACS. IIT allow to shed light on the true mechanism of ACS without significant obstructive coronary disease. Finally, in case of conservative approach, close in–hospital monitoring is mandatory, given the highest probability of complications in the first days after clinical onset.